Tindaya Variations - Isaac Marrero Guillamón (Journal of Anthropological Films)
The mountain of Tindaya (Fuerteventura, Canary Islands) has been entangled in controversy for over thirty years. The mountain is, at once, a sacred site for the indigenous people of Fuerteventura– who decorated it with hundreds of engravings–; a mining resource where trachyte rock is extracted; and the proposed location of a monumental artwork consisting of a huge cubic cave dug into its interior. Tindaya Variations follows the traces of the conflict against a background of everyday activities, tourist landscapes and post-crisis ruins– revealing, in the process, the tensions between environmental conservation, indigenous heritage and development-oriented futures.